The effect of blood flow restriction training combined with electrical muscle stimulation on neuromuscular adaptation: a randomized controlled trial - Li, Na; Yang, Jingfeng; Liao, Yuanpeng (Frontiers in Physiology, 2023)
Objective: Low-intensity resistance training (≤25% 1RM) combined with blood flow restriction training (BFRT) is beneficial to increasing muscle mass and muscle strength, but it cannot produce increased muscle activation and neuromuscular adaptation, as traditional high-intensity strength training does. The purpose of this study is to investigate the effects of independently applying BFRT and electrical muscle stimulation (EMS), as well as combining the two methods, on muscle function. Methods: Forty healthy participants with irregular exercise experiences were randomly assigned to four groups: BFRT-alone group (BFRT, n=10), EMS-alone group (EMS, n=10), BFRT combined with EMS group (CMB, n=10), and the control group (CTR, n=10). All participants received low-intensity squat training at a load of 25% 1RM 5 times/week for 6 weeks. Cross-sectional area (CSA) and electromyographic root mean square (RMS) in the rectus femoris, as well as peak torque (PT) of the knee extensor, were measured before and following a 6-week intervention. Results: Following the 6-week intervention, the increases in muscle activation in the CMB group were statistically higher than those in the BFRT group (p < 0.001), but not different from those in the EMS group (p = 0.986). Conclusion: These data suggest that the combination of BFRT and EMS for low-intensity squat training improved the muscle strength of the lower limbs by promoting muscle hypertrophy and improving muscle activation, likely because such a combination compensates for the limitations and deficiencies of the two intervention methods when applied alone.